Optimizing the outcomes of pancreatic cancer surgery - Strobel, Oliver; Neoptolemos, John P.; Jäger, Dirk; Büchler, Markus W. (Nature reviews. Clinical oncology, 2019)
Successful surgical resection offers patients with pancreatic cancer the best chance of survival. However, many patients do not have surgically resectable disease. In this Review, the authors describe recent improvements in pancreatic cancer surgery, which have increased survival and also enabled more patients to undergo surgery.
Published: 19 October 2018
Gesehen am 23.07.2019